Spray‐Drying and Atomic Layer Deposition: Complementary Tools toward Fully Orthogonal Control of Bulk Composition and Surface Identity of Multifunctional Supraparticles. Issue 1 (21st November 2021) - Müssig, Stephan; Koch, Vanessa M.; Collados Cuadrado, Carlos; Bachmann, Julien; Thommes, Matthias; Barr, Maïssa K. S.; Mandel, Karl
Abstract: Spray‐drying is a scalable process enabling one to assemble freely chosen nanoparticles into supraparticles. Atomic layer deposition (ALD) allows for controlled thin film deposition of a vast variety of materials including exotic ones that can hardly be synthesized by wet chemical methods. The properties of coated supraparticles are defined not only by the nanoparticle material chosen and the nanostructure adjusted during spray‐drying but also by surface functionalities modified by ALD, if ALD is capable of modifying not only the outer surfaces but also surfaces buried inside the porous supraparticle. Simultaneously, surface accessibility in the porous supraparticles must be ensured to make use of all functionalized surfaces. In this work, iron oxide supraparticles are utilized as a model substrate as their magnetic properties enable the use of advanced magnetic characterization methods. Detailed information about the structural evolution upon individual ALD cycles of aluminium oxide, zinc oxide and titanium dioxide are thereby revealed and confirmed by gas sorption analyses. This demonstrates a powerful and versatile approach to freely designing the functionality of future materials by combination of spray‐drying and ALD. Abstract : Spray‐drying is a scalable process that enables one to assemble freely chosen nanoparticles into supraparticles, i.e., microparticles with adjustable nanostructure. Atomic layer deposition is used to deposit controlled thin films of different materials onto and within supraparticles. The combination of these two techniques demonstrated in this work allows for the independent adjustment of properties determined by bulk and surface composition.